Development of Flood Disaster Management Module as a Means of Elementary School Learning Enrichment - Kiki Aryaningrum; Arief Kuswidyanarko; Ali Fakhrudin; Aldora Pratama; Husnil Kirom; Siti Rachmi Indah Sari; Ahmad Adi Suhendra (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
This study aims to develop a flood disaster management module as a means of enriching elementary school learning. This development research aims to develop a flood disaster management module and the feasibility of the flood disaster management module media as a means of enriching elementary school learning. The method in this study was carried out using the Borg and Gall Research & Development model which has been modified by Sugiyono covering 7 stages, namely: 1) potentials and problems, 2) collecting data, 3) product design, 4) design validation, 5) design revision, 6) product trials, 7) product revisions. The results of this study indicate that the results obtained from the validation of material experts obtained an average of 81% with the